Response of soil microbial communities to mixed beech-conifer forests varies with site conditions - Lu, Jing-Zhong; Scheu, Stefan (Soil biology & biochemistry, 2021)
Tree - soil interactions depend on environmental conditions. Planting trees may affect soil microbial communities and compromise their functioning, particularly in unfavorable environments. To understand the effects of tree species composition on soil microbial communities, we quantified structural and functional responses of soil microorganisms to tree species planted in various environments using substrate-induced respiration and phospholipid fatty acid analyses. Five forest types were studied including pure stands of native European beech (Fagus sylvatica), range expanding Norway spruce (Picea abies), and non-native Douglas-fir (Pseudotsuga menziesii), as well as the two conifer - beech mixtures. We found that microbial functioning depends strongly on soil nutrient concentrations in the studied forest sites. At nutrient-poor sites, soil microorganisms were more stressed in pure and mixed coniferous forests, especially in Douglas-fir, compared to beech forests. By contrast, microbial structure and functional indicators in beech forests varied little with site conditions, likely because beech provided ample amounts of root-derived resources for microbial growth. Since soil microbial communities are sensitive to Douglas-fir, planting Douglas-fir may compromise ecosystem functioning, especially at nutrient-poor sites. Overall, root-derived resources are important for determining the structure and functioning of soil microbial communities, so soil microbial responses to tree species will depend upon the provisioning of these resources as well as site-specific environmental conditions. •Soil microorganisms do not respond to forest types at nutrient-rich sites.•European beech mitigates microbial stress in nutrient-poor forest soils.•Microbial stress in nutrient-poor forest soils is intensified by planting Douglas-fir.•Admixing conifers to beech compromises microbial functioning at nutrient-poor sites.